Development of Interactive Learning Videos for Arabic Reading Proficiency Using Videopad and Edpuzzle Aplications - Sri Wahyuni; Nurlaila (INGGARA (Jurnal Pendidikan Bahasa Inggris dan Bahasa Arab), 2024)
The purpose of this study was to determine the validity and practicality of interactive learning videos for Arabic reading proficiency developed using VideoPad and Edpuzzle applications. The type of research used is research and development (R&D). Data were collected through validity and practicality questionnaires. The data were analysed quantitatively descriptively. The research test subjects were students of MTs Muhammadiyah Sulit Air Solok West Sumatra. The results of this study indicate that the interactive learning video for Arabic reading proficiency developed using the VideoPad and Edpuzzle applications is very valid with a validation score on the aspect of learning material 97.5%, on the aspect of learning media 93.75%, and on the aspect of video language 97.5%. The average validation score is 96.25%. The results of the practicality test of the interactive learning video for Arabic reading proficiency developed using VideoPad and Edpuzzle applications show that the video is very practical according to the assessment of teachers and students with a practicality score from teachers of 85% and a practicality score from students of 80.7%. Thus it can be concluded that the interactive learning video developed using VideoPad and Edpuzzle applications can be used for Arabic reading proficiency learning for Madrasah Tsanawiyah (MTs) students.